Effects of age and comorbidity on treatment and survival of patients with muscle‐invasive bladder cancer. Issue 4 (25th January 2014) - Goossens‐Laan, Catharina A.; Leliveld, Anna M.; Verhoeven, Rob H.A.; Kil, Paul J.M.; de Bock, Geertruida H.; Hulshof, Maarten C.C.M.; de Jong, Igle J.; Coebergh, Jan Willem W.
<x xml:space="preserve">Abstract</x> Our study assessed whether rising age, socioeconomic status (SES) and the presence of serious comorbidity affected treatment choice and survival in a population‐based series of patients with muscle‐invasive bladder cancer (MIBC) in The Netherlands. Therefore, a consecutive series was studied, including all patients diagnosed with MIBC between 1995 and 2009 in the Eindhoven Cancer Registry, preceding centralization of cystectomy. The independent effects of age, SES and serious comorbidity on therapy choice and their effects on overall survival were estimated by multivariate logistic regression and multivariate Cox proportional hazard analyses, respectively. Out of the 2, 445 patients, 38% were aged ≥75 years at diagnosis and 63% had at least one serious comorbid condition. Higher age and serious comorbidity were independent predictors for abstaining from cystectomy, where SES was not (61–74 vs. ≤60: odds ratio [OR], 0.8; 95% confidence interval [CI], 0.6–1.0; ≥75 vs. ≤60: OR, 0.1; 95% CI, 0.1–0.2; one comorbid condition vs. none: OR, 0.7; 95% CI, 0.5–0.9; two vs. none: OR, 0.6; 95% CI, 0.5–0.8). Patients undergoing cystectomy, external beam radiotherapy or interstitial radiotherapy survived longer independent of age, SES and serious comorbidity (hazard ratio [HR]: 0.4; 95% CI: 0.4–0.5; HR: 0.8; 95% CI: 0.7–0.9; HR: 0.4; 95% CI: 0.3–0.5, respectively). Consequently, preceding centralization of cystectomy, higher age and serious comorbidity were independent predictors for abstaining from cystectomy owing to an expected high rate of short‐term medical problems. As cystectomy is associated with a better survival, independently of age, SES and serious comorbidity, it can be questioned whether cystectomy has been underutilised in elderly and in patients with serious comorbidity. Centralization might be a solution for this suggested underutilisation.